Optimizing nanostructure to achieve high dielectric response with low loss in strongly dipolar polymers. (September 2015) - Thakur, Yash; Dong, Rui; Lin, Minren; Wu, Shan; Cheng, Zhaoxi; Hou, Ying; Bernholc, J.; Zhang, Q.M.
Abstract: Advances in modern electronics require the development of polymer-based dielectric materials with high dielectric constant, low dielectric loss, and high thermal stability. Fundamental dielectric theory suggests that strongly dipolar polymers have the potential to realize a high dielectric constant. In order to achieve high thermal stability, these polymers should also possess a high glass transition temperature T g . However, it has been observed that in many dielectric polymers the dielectric constant decreases markedly at temperatures below T g due to dipole freezing. This study shows, through combined theoretical and experimental investigations, that nano-structure engineering of a weakly-coupled strongly-dipolar polymer can result in a high energy density polymer with low loss and high operating temperature. Our studies reveal that disorder creates a significantly larger free volume at temperatures far below T g, enabling easier reorientation of dipoles in response to an electric field in aromatic urea and thiourea polymers. The net result is a substantial enhancement in the dielectric constant while preserving low dielectric loss and very high breakdown field. These results here pave the way for engineering the nanostructure to create high energy density polymers with low loss and high operating temperature. Graphical abstract: Highlights: Improvement in dielectric properties of strongly dipolar polymers. Introduction of free volume to achieve high dielectric response in the glass state. Disorder is introduced to create large free volume. Improved dielectric properties demonstrated in disordered meta-phenylene polyurea.